Peningkatan Hasil Belajar Senam Lantai Menggunakan Metode Demonstrasi dan Penugasan Berbasis Google Formulir - Dwi Arif Stiyapranomo (Universitas Mercu Buana Yogyakarta, 2022)
This study aims to determine the Improvement of Floor Gymnastics Learning Outcomes Using Google Form-Based Demonstration and Assignment Methods. This type of research is a type of classroom action research. The subjects of this study were students of MTsN 3 Bantul class VIII D, totaling 30 children consisting of 17 girls and 13 boys. Data collection techniques used include: interviews, tests, questionnaires, observation, or documentation studies. The instruments used for data collection in this study were observation guidelines for teachers, observation guidelines for students, and questionnaires for students, as well as learning materials for floor exercise activities for class VIII D MTsN 3 Bantul. Analysis of the data used is descriptive quantitative analysis. Based on the results of the research from cycles I and II, it can be concluded that the process of assessing student learning outcomes in class VIII D MTsN 3 Bantul obtained as many as 24 children who passed the KKM in the knowledge aspect or reached 80%. And in the assessment of the skills aspect, 25 children were declared to have passed the KKM in the skills aspect or reached 83.33%. Based on these data, it can be concluded that the percentage of students' achievement in learning outcomes in the application of demonstration methods and assignments assisted by VPAMS-ppt learning media in cycle II reaches above 75% with a KKM value of 75. This is because in the second cycle research has applied improvement in the learning process based on Cycle I observations.